2004
DOI: 10.1089/hyb.2004.23.373
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Quantitative Cell-Based Intracellular ELISA for the Screening of B Cell Hybridoma Supernatants: A Novel Rapid Assay to Detect Positive Clones

Abstract: The primary screening of hybridoma clones secreting monoclonal antibodies (MAbs) requires the testing of a large number of hybridoma culture supernatants within a short time and is very labor-intensive. In addition, the type of antigen and its location in the cell have to be considered when selecting the appropriate screening procedure, but relatively few reagents are available for analyzing these molecules. We have developed an intracellular and cell surface ELISA technique for screening hybridoma supernatant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
(18 reference statements)
0
8
0
1
Order By: Relevance
“…57 We were able to detect significant differences in vivo regarding tumor growth and mouse survival (Fig. 2), although the overall level of CD1d on the cell surface of RMA/S-CD1 cells was about 62% greater (as measured by the 8F3 antibody 24 ) than the RMA/ S-V line (Fig. 1).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…57 We were able to detect significant differences in vivo regarding tumor growth and mouse survival (Fig. 2), although the overall level of CD1d on the cell surface of RMA/S-CD1 cells was about 62% greater (as measured by the 8F3 antibody 24 ) than the RMA/ S-V line (Fig. 1).…”
Section: Discussionmentioning
confidence: 92%
“…Thus, how does this difference manifest itself in the observations reported here? When we stained these two lines with a panel of 10 mouse CD1d-specific mAb (which have distinct epitope specificities for the murine CD1d1 molecule, 24 and data not shown), it was apparent that the staining patterns were different when compared to that observed with CD1d-transfected murine L cells (data not shown). This suggested that there were both quantitative and especially ''qualitative'' differences between the two tumor-cell lines; namely, the RMA/S lipids that are presented by CD1d to NKT cells may be inhibitory in nature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Normal rat serum was purchased from Sigma-Aldrich (St. Louis, MO). The anti-mouse CD1d1 mAbs: 1H6 [25], 1E2, 8F3, 9E4, and 1A8 generated by us have been described previously [29]. The anti-MHC class I (K b ) exon-8 specific rabbit antiserum and human TAP1-expressing recombinant vaccinia virus (VV) [30] were kindly provided by Drs.…”
Section: Methodsmentioning
confidence: 99%
“…8 ␣-and ␤-galactosylceramides (GalCer) were purchased from Enzo Life Sciences. Anti-CD1d Abs were: 1B1, 20 1H6, 21 1A8, 22 1E2, 22 6F7, 22 and 9G1 22 and isotype-matched controls were generated as described previously.…”
Section: Reagentsmentioning
confidence: 99%